Introduction of Aerobic Kids Gymnastics to Improve Teacher Understanding and Motoric Development of Kindergarten Laboratory Students in Nusantara University PGRI Kediri - Reo Prasetiyo Herpandika; Hendra Mashuri; Rendhitya Prima Putra; Budiman Agung Pratama; Irwan Setiyawan (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2020)
Kindergarten is the right place to develop children's motor skills. The age of kindergarten students is the age of play, where students have a high urge to do physical activities that are fun. Therefore there is a need for physical activity that is fun and can improve children's fitness and motor skills. Aerobic Kids Gymnastics is a physical activity that pays attention to aspects of children's body movements and children's biomechanics wrapped in a pleasant atmosphere, so that in Aerobic Kids gymnastic activities, students will feel joy when moving. TK Nusantara University Laboratory PGRI (UNP) Kediri is an educational institution whose ambition is to create superior human resources by developing motor skills from an early age. Therefore, the introduction of aerobic kids gymnastics activities is very suitable for students' motor development and the understanding of kindergarten UNP Lab Kediri teachers. The introduction of Aerobic Kids Gymnastics to Enhance Teacher Understanding and Motor Children's Development in TK Kediri UNP Laboratory is a positive effort to improve teachers' understanding of students' motor development and improve students' motor skills. The results of this activity indicate an increase in teacher understanding of gymnastic movements that are appropriate to students' motor development. Kindergarten UNP Kediri Laboratory Kindergarten teachers understand the movements needed by kindergarten age students to develop motor skills. The Kediri UNP Laboratory Kindergarten teacher also developed a number of movements that were felt to be appropriate to the character of the students and the needs of the students' environment.